2005
DOI: 10.1002/rcm.1908
|View full text |Cite
|
Sign up to set email alerts
|

Technical considerations for the use of 15N‐DNA stable‐isotope probing for functional microbial activity in soils

Abstract: Stable-isotope DNA probing is a culture-independent technique that may provide a link between function and phylogeny of active microorganisms. The technique has been used in association with 13C substrates while here we evaluate feasibility and limitations of 15N-DNA stable-isotope probing (SIP) using labelled and unlabelled pure microbial cultures or soil extracts. Our results showed that (15)N-DNA probing is feasible for cultures as well as soil samples. Limitations of 15N-DNA-SIP are (a) the need for relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 12 publications
2
32
1
Order By: Relevance
“…Our results also demonstrated that the use of SYBR safe™ with the Safe Imager™ blue light transilluminator provided a sensitive detection of DNA in CsCl density gradients. While we were not able to detect less than 2μg of DNAwith EtBr (data not shown) and detection limits between 0.5 and 2μg have been reported by others for EtBr (Cadisch et al, 2005;Neufeld et al, 2007), we were able to visualize a band containing amounts as low as 100ng of DNA using SYBR safe™. This increased sensitivity can play an important role in SIP analysis, where the labelling of DNA with 13 C can be challenging.…”
contrasting
confidence: 40%
“…Our results also demonstrated that the use of SYBR safe™ with the Safe Imager™ blue light transilluminator provided a sensitive detection of DNA in CsCl density gradients. While we were not able to detect less than 2μg of DNAwith EtBr (data not shown) and detection limits between 0.5 and 2μg have been reported by others for EtBr (Cadisch et al, 2005;Neufeld et al, 2007), we were able to visualize a band containing amounts as low as 100ng of DNA using SYBR safe™. This increased sensitivity can play an important role in SIP analysis, where the labelling of DNA with 13 C can be challenging.…”
contrasting
confidence: 40%
“…In a recent study of soil cellulolytic bacteria, the 13 Clabelled cellulose was purified from the growth medium of Acetobacter xylinus, which was grown on 13 C-glucose as a sole source of carbon (el Zahar Haichar et al, 2007). Finally, 13 CO 2 -labelling of plants represents a clever approach to tracking plant-derived carbon to microorganisms in the rhizosphere (Cadisch et al, 2005;Lu and Conrad, 2005;Rangel-Castro et al, 2005). Such creative chemical and biological synthesis of complex organic compounds widens the application and versatility of SIP.…”
Section: Stable-isotope Probingmentioning
confidence: 99%
“…One recent advance has involved improvements to the labelling and detection of DNA using 15 N-labelled substrates (Cadisch et al, 2005). The resolution of labelled and unlabelled DNA (or RNA) following 15 N incorporation is less than that for 13 C incorporation (Cupples et al, 2006), reflecting the differential abundance of nitrogen and carbon in DNA, respectively.…”
Section: Stable-isotope Probingmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, with some notable exceptions (6,7,36,41), most analyses have focused on substrates labeled with 13 C, offering better resolution of labeled and unlabeled nucleic acids than can be achieved with the smaller increases in buoyant density (BD) from 15 N incorporation (1,11). In particular, small changes in density with 15 N incorporation may not be sufficient to differentiate labeled DNA from unlabeled DNA of high GϩC content (1,6,8,11). Although analysis can be improved by using AT-selective intercalating dyes which exaggerate GϩC bias (6,7,19), because the distribution of nucleic acids is Gaussian (28), nucleic acids derived from an abundant population are often distributed throughout a gradient.…”
mentioning
confidence: 99%